Effects of ICT use on self-regulated learning: chain intermediary effect of information retrieval and social interaction - Wang, Meiqian; Zhang, Shuping; Huang, Mengyuan; Zhang, Heping (Frontiers in Psychology, 2025)
IntroductionSelf-regulated learning (SRL) is a crucial competency in today’s rapidly evolving digital society. Information and communication technologies (ICT) offer unprecedented opportunities to enhance SRL. However, the relationship between ICT use and SRL remains contentious. Understanding how ICT use affects teenagers’ SRL through cognitive and social pathways is essential for guiding healthy digital learning habits. This study examined the relationship between ICT use and SRL among teenagers by investigating the chain mediating roles of information retrieval and social interaction, aiming to identify optimal ways for adolescents to benefit from digital learning.MethodsA chain mediating effect were analyzed using a Hong Kong sample taken from the Programme for International Student Assessment (PISA) 2022 data pertaining to 4,378 15-year-old students from 163 schools.ResultsThe results indicated that (1) ICT use was positively correlated with SRL (β = 0.28, p < 0.001), (2) information retrieval and social interaction played independent mediating roles in the relationship between ICT use and SRL (effect values: 0.035 and 0.006, respectively), and (3) there was a chain effect between ICT use and SRL mediated by information retrieval and social interaction, with a total effect value of 0.235.DiscussionThe study contributed to the existing theoretical framework by empirically validating a chain mediation model that integrated cognitive and social dimensions, thereby offering a more comprehensive understanding of the mechanisms through which ICT use influenced SRL. These findings could provide insightful information to the implementation of educational decisions to administer ICT tools to facilitate students’ SRL process.